Heparinization Versus Salinization in fully implant Catheter: Integrative Review - Silva, Ricardo da (2023)
Evaluate the effectiveness of salinization compared to heparinization on the patency of the fully implanted catheter. Integrative literature review. The search was carried out in the National Library of Medicine, Science Direct, Scientific Electronic Library Online and Virtual Health Library databases. When washing the port-a-cath, 10 to 20ml of 0.9% saline solution is used, reaching up to 20 ml for washing; in blocking, 0.9% saline solution is used to saline or heparinized solution, with concentrations of 50 to 100U/ml, reaching up to 500U/ml for heparinization, both with a 1.5 to 5 ml flush. SF stood out by showing security in port-a-cath blocking. The use of a fully implanted catheter in cancer patients proved to be of such importance for the procedures, the studies showed that there is no significant difference between the solutions, suggesting the use of 0.9% saline solution for catheter blocking.